The organosolv fractionation of cork components - Cordeiro, N.; Neto, C. P.; Rocha, J.; Belgacem, M. N.; Gandini, A. (HOLZFORSCHUNG, 2002)
Extractive-free cork from Quercus suber L. was submitted to organosolv fractionation and the effects of different process variables, such as ethanol/water ratio, temperature, time and the presence of acidic or alkaline catalysts, were studied. The variation of the relative proportions of extracted components, as a function of the processing conditions, could thus be established. Whereas the addition of 0.1 M acetic acid only increased the yield of extracted materials from about 15 to 23 %, the use of sodium hydroxide, at the same concentration, produced a jump to 76 %. In the case of the alkaline organosolv fractionation. an increase in process temperature, time and catalyst concentration led to an increase in the extraction yield, although in some cases this increase did not follow a sustained trend, as in the case of reaction time. Increasing the ethanol/water ratio led to a higher selectivity in favour of suberin extraction. Residual cork from different organosolv processes was characterised by FTIR and C-13 solid-state NMR. The latter technique provided some valuable information about both process selectivity and cork morphology, particularly with respect to the positioning of suberin macromolecules in the cell wall.
The following values have no corresponding Zotero field: pub-location: GENTHINER STRASSE 13, D-10785 BERLIN, GERMANY publisher: WALTER DE GRUYTER & CO
Keywords: C-13 NMR; Cork; ethanol/water extraction; FTIR; organosolv fractionation; Quercus Suber L; suberin